Influence analysis supportive educational nursing towards knowledge about TB disease in pulmonary TB sufferers - Muhtar Muhtar; Aniharyati Aniharyati; Dian Vitasari; Kushariyadi, (International Journal of Scientific Research and Management (IJSRM), 2024)
Tuberculosis (TB) is an infectious disease which is one of the 10 main causes of death worldwide and is the main cause of death due to infectious diseases. The researcher aims to further explore the influence of family-based supportive-educative nursing interventions on increasing the knowledge of pulmonary TB sufferers in the city of Bima. This research used a quasi-experimental design in the form of a pretest-posttest with control group design. SampleinstudyThese are all pulmonary TB sufferers who are undergoing TB treatment from June to September 2023 who meet the inclusion and exclusion criteria. ficay and compliance with swallowing medication from the pre-test and post-test results given to the treatment group and the control group. The alternative hypothesis is accepted if the p value is ≤ 0.05. The knowledge of pulmonary TB sufferers from the post test results in the treatment group is mostly in the good category, while in the control group most of it is in the sufficient category. Increasing the knowledge of patients and their families in caring for pulmonary TB sufferers in the treatment group cannot be separated from the provision of knowledge about the concept of pulmonary TB disease, treatment of pulmonary TB disease, and self-care activities for pulmonary TB sufferers provided during treatment using health education, guidance and counseling methods. as well as demonstrations of ways to self-care for pulmonary TB sufferers at home.